2022
DOI: 10.1155/2022/7731618
|View full text |Cite|
|
Sign up to set email alerts
|

Gauging the Impact of Artificial Intelligence and Mathematical Modeling in Response to the COVID-19 Pandemic: A Systematic Review

Abstract: While the world continues to grapple with the devastating effects of the SARS-nCoV-2 virus, different scientific groups, including researchers from different parts of the world, are trying to collaborate to discover solutions to prevent the spread of the COVID-19 virus permanently. Henceforth, the current study envisions the analysis of predictive models that employ machine learning techniques and mathematical modeling to mitigate the spread of COVID-19. A systematic literature review (SLR) has been conducted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 85 publications
0
10
0
1
Order By: Relevance
“…The most common ML methods in the reviewed studies were CNN 34–85 . In line with this result, other review studies also indicated CNN to be the most common method to develop a system for COVID‐19 diagnosis 23,25,27,28,30,100 . A CNN is a type of DL algorithm used for processing medical images, particularly for identifying specific features in chest radiographs of COVID‐19 patients 30 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The most common ML methods in the reviewed studies were CNN 34–85 . In line with this result, other review studies also indicated CNN to be the most common method to develop a system for COVID‐19 diagnosis 23,25,27,28,30,100 . A CNN is a type of DL algorithm used for processing medical images, particularly for identifying specific features in chest radiographs of COVID‐19 patients 30 .…”
Section: Discussionmentioning
confidence: 74%
“…In line with this result, other review studies also indicated CNN to be the most common method to develop a system for COVID-19 diagnosis. 23,25,27,28,30,100 A CNN is a type of DL algorithm used for processing medical images, particularly for identifying specific features in chest radiographs of COVID-19 patients. 30 CNN is more valuable than other methods for developing CDSS due to its excellent performance accuracy and much lower preprocessing.…”
Section: Nonknowledge-based Cdssmentioning
confidence: 99%
“…In [22], the proposed iCovidCare model increases the prediction ratio by 89% and with the training and testing accuracy of 95.13% and 91.68%. In [23], using Capnobase and sEMG datasets with Bi-LSTM + Attn gives the best results, and using MIMIC II dataset with 2-Layer LSTM gives the best results over CNN-LSTM. Also found that the 64s window showed more accurate results than the 32s window, and the trend showed that performance increased as the size of the window increased.…”
Section: Time Series Modelsmentioning
confidence: 98%
“…These questions were framed by considering the demands of research questions. The quality assessment questions framework has already been used in several earlier SLRs (Hassan et al, 2022, Haafza et al, 2021, Saleem et al, 2022. In this SLR, we have considered six questions that demand objectivity: the topic's context, data sources, limitations or gaps, discussion of future directions, and performance evaluation criteria used in the selected studies.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Since the beginning of October 2021, the infection rate has surged tenfold. There has been an unexpected spike in infections and a likely spike in the proportion of hospital admissions and fatalities, having a detrimental effect on healthcare resources [30,31]. It is the nature of the viruses to mutate; henceforth emergence of new variants with time cannot be overlooked.…”
Section: A Which Vaccines Are Efficient Against Emerging Viral Strain...mentioning
confidence: 99%